2018
DOI: 10.5688/ajpe6701
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating an Entrepreneurial Certificate into the Pharmacy Curriculum

Abstract: Objective. Describe the implementation and assessment of an entrepreneurial certificate program within an electiveMethods. An entrepreneurial certificate program through the Kauffman Foundation was integrated within an entrepreneurial elective to provide students at Presbyterian College School of Pharmacy to receive more in depth training regarding entrepreneurial skills. A pre-/post-survey was administered to assess knowledge and skills obtained.Results. Thirty-three students completed the pre-/post-survey wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Standard 4.3 on innovation and entrepreneurship suggests that students engage in innovative activities by using creative thinking to envision better ways to accomplish professional goals. As a result, a number of pharmacy schools have integrated innovation and entrepreneurship courses into their curricula either as part of a joint MBA/PharmD degree or as business or entrepreneurial certificates (Shealy and McCaslan, 2018).…”
Section: Acpe Standards On Entrepreneurship and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard 4.3 on innovation and entrepreneurship suggests that students engage in innovative activities by using creative thinking to envision better ways to accomplish professional goals. As a result, a number of pharmacy schools have integrated innovation and entrepreneurship courses into their curricula either as part of a joint MBA/PharmD degree or as business or entrepreneurial certificates (Shealy and McCaslan, 2018).…”
Section: Acpe Standards On Entrepreneurship and Innovationmentioning
confidence: 99%
“…But first, it is critical that current and future pharmacists gain the knowledge and training necessary to become entrepreneurs. A recent study found that incorporating an entrepreneurial certificate program in the curriculum increased students’ confidence in entrepreneurial principles and skills (Shealy and McCaslan, 2018). There is also evidence that a growing number of pharmacists prefer to seek business or entrepreneurial training at business schools after they have entered the workforce (Alkhateeb et al, 2012).…”
Section: Pharmacist Impact On Healthcare Expenditurementioning
confidence: 99%
“…As a result, the Accreditation Council for Pharmacy Education incorporated entrepreneurship in pharmacy education professional standards in 2016 (ACPE, 2015), and a number of universities began providing entrepreneurship tracks for pharmacy students in the USA, covering topics such as process innovation, new product development, business intelligence and continuous improvement (University of Maryland School of Pharmacy, 2021). Other programs offer certificates in entrepreneurship for pharmacy students; Shealy and McCaslan (2018) describe such a certificate program at Presbyterian College of Pharmacy and find that student confidence in entrepreneurship knowledge and skills was higher for students who obtained the certificate.…”
Section: Introductionmentioning
confidence: 99%